Preparation of porous dry-method electrode for electrolyzing water, electrode plate and application
By introducing pore-forming agent into the electrode to form a porous structure, the problem of decreasing porosity during dry electrode molding is solved, and the efficiency and electrochemical performance of electrolytic water are improved.
Patent Information
- Application Number
- CN202411607728.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-12
AI Technical Summary
During the dry electrode forming process, as the thickness or compaction density of the electrode sheet increases, the porosity will gradually decrease, affecting the utilization rate of the catalyst, the wetting properties of the electrolyte in the electrode sheet, and the transmission resistance of the electrolytic water gaseous products, thereby affecting the water electrolytic performance.
By introducing a pore-forming agent into the electrode, the porous electrode is formed by drying or infiltration, the pore structure of the electrode sheet is adjusted, the number of catalytic active sites is increased, and the electrode is maintained with a large compaction density or thickness.
While maintaining the compaction density and thickness of the electrode, the porosity and pore size distribution of the electrode are improved, the permeability of the electrolyte and the diffusion performance of the gas are enhanced, and the efficiency and electrochemical performance of the electrolytic water are improved.
Smart Images

Figure CN119506933A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water electrolysis, and in particular to a method for preparing a porous dry electrode. Background Art
[0002] As the global energy transition accelerates, hydrogen energy, as a green and pollution-free energy carrier, is considered to be one of the key energy options in the future. Water electrolysis technology can achieve efficient conversion of hydrogen energy and electrical energy, and is expected to serve as an important means of regulating wind and photovoltaic power generation.
[0003] Among them, the design and preparation process of the electrode plays a vital role in the electrochemical performance of the entire water electrolysis system. Usually, electrodes are generally prepared by a wet process. This method is based on a solvent method to form a uniformly mixed electrode slurry, and then forms an electrode by drying. This not only increases the complexity of production, but also has an adverse effect on the environment during the drying process of the solvent. In order to overcome these shortcomings, the dry process has gradually developed. The dry process preparation process avoids the use of solvents and manufactures electrodes by directly rolling the powder material into shape. Such a process greatly simplifies the production process, reduces energy consumption, and reduces environmental pollution.
[0004] However, during the dry electrode forming process, as the thickness or compaction density of the electrode increases, the porosity will gradually decrease, affecting the utilization of the catalyst, the wettability of the electrolyte in the electrode, and the transmission resistance of the gaseous products of electrolyzed water, thereby affecting the water electrolysis performance. Adjusting the pore structure of the electrode can increase the number of catalytic active sites and maintain a large compaction density or thickness of the electrode without adding additional mass transfer resistance.
[0005] Therefore, it is technically necessary to propose an improved method for preparing porous dry electrodes to avoid the known shortcomings of the prior art. More specifically, in order to overcome the contradiction between electrode compaction density, thickness and porosity, we developed a porous dry electrode by introducing a pore former into the electrode and forming a porous electrode by drying or infiltration. The preparation method is simple and easy, with low manufacturing cost, and is suitable for industrial production applications. Summary of the invention
[0006] The invention relates to a method for preparing a porous dry electrode for electrolyzing water.
[0007] The porous dry electrode preparation method of the present invention is characterized in that the preparation steps are as follows:
[0008] (1) adding powdered active substances and powdered binders into a mixer for mixing;
[0009] (2) adding a pore-forming agent to the powder mixture obtained in step (1) and mixing the mixture using a mixer;
[0010] (3) crushing the powder mixture obtained in step (2) by a crusher to obtain a powder mixture of powder active material, powder binder and powder pore former with uniform particle size distribution;
[0011] (4) passing the powder mixture obtained in step (3) through a twin-screw extruder or an open mill to provide high shear force to fiberize the powder binder, thereby forming the powder mixture into a sheet;
[0012] (5) The sheet obtained in step (4) is rolled at 50-120°C to form a 10 μm-500 μm electrode film; the compaction density is 40.0 mg / cm 3 -500.0mg / cm 3 ;
[0013] (6) Finally, the dry electrode including the electrode film obtained in step (5) is treated by one of the following methods to obtain a porous dry electrode:
[0014] a) when the pore-forming agent added in step (2) is a pore-forming agent, the electrode is heated and dried to decompose and release the pore-forming agent, thereby forming a porous structure in the electrode, or
[0015] b) When the pore-forming agent added in step (2) is an alkali or salt powder of an electrolyte used for electrolysis of water, the solute powder in the electrode is dissolved in the solvent by contacting the electrode with the corresponding electrolyte, thereby forming a porous electrode structure.
[0016] The mass fractions of the powder active substance, the powder binder and the pore former are 60wt%-96wt%, 2wt%-20wt% and 2wt%-20wt% respectively;
[0017] The pore former is a mixture of one or more of ammonium bicarbonate, ammonium carbonate, urea and oxalic acid in any proportion. The selection of the pore former should be optimized according to the target porosity and mechanical strength of the electrode to ensure that the electrode has a suitable pore size distribution and electrolyte permeability in the electrode application.
[0018] The heating and drying is vacuum drying, the heating and drying temperature is 70° C. to 180° C., and the heating and drying time is 10 h to 24 h.
[0019] The alkali and salt powders are solute powders of electrolytes used in electrolysis of water.
[0020] The electrodes are contacted with the corresponding electrolytes by immersing the electrodes alone in the corresponding electrolytes, or by circulating electrolytes in the electrode flow channels after being assembled into an electrolytic cell as a whole, and the immersion or circulation time is 12 hours to 48 hours.
[0021] Compared with the prior art, the advantage of the present invention is that it provides a method for adjusting the pore structure of a dry electrode, so that the electrode has more excellent electrochemical performance.
[0022] The porous dry electrode preparation method is simple and easy, has low manufacturing cost, and is suitable for industrial production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A schematic diagram of a porous dry electrode used in the field of water electrolysis technology;
[0024] Figure 2 The performance curves of the electrolytic cells corresponding to Example 1 and Comparative Example 1 at 2V;
[0025] Figure 3 The performance curves of the electrolytic cells corresponding to Example 3 and Comparative Example 3 at 1.9V are shown. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0027] The following embodiment provides a method for preparing a porous dry electrode for use in the field of water electrolysis technology. First, 60wt%-96wt% of powdered active material and 2wt%-20wt% of powdered binder are added to a mixer and mixed for 0.5-5h at a speed of 20-1000r / min and a stirring temperature of 20-80°C; secondly, 2wt%-20wt% of pore-forming agent is added and mixed by a mixer for 0.5-2h at a speed of 50-800r / min and a stirring temperature of 2 0-80℃; then pulverize it through a pulverizer to obtain a powder mixture of powder active material, powder binder and powder pore former with uniform particle size distribution; pass the obtained powder mixture through a twin-screw extruder or an open mill to provide high shear force to fiberize the powder binder, so that the powder mixture is formed into a sheet; the molding temperature is controlled at 20-80℃; then roll the obtained sheet at 50-120℃ to form a 10μm-500μm pole film; the compaction density is 40.0mg / cm 3 -500.0mg / cm 3 Finally, the dry electrode plate containing the plate film is heated and dried to decompose and release the pore-forming agent, thereby forming a porous structure in the electrode.
[0028] The pore-forming agent is a mixture of one or more of ammonium bicarbonate, ammonium carbonate, urea and oxalic acid in any proportion.
[0029] The heating and drying is vacuum drying, the heating and drying temperature is 70° C. to 180° C., and the heating and drying time is 10 h to 24 h.
[0030] Example 1
[0031] A method for preparing a porous dry electrode for use in the field of water electrolysis, comprising the following steps:
[0032] (1) 90 wt% FeCoNi high entropy alloy powder active material (particle size 15-53 μm, Shanghai Yanbei New Material Technology Co., Ltd.) and 5 wt% PTFE powder binder were added to a three-dimensional mixer for mixing. The mixing time was set to 3 h, the mixer speed was 500 r / min, and the stirring temperature was set to 30 °C to ensure that the powder and the binder were evenly mixed.
[0033] (2) The powder mixture obtained in step (1) and 5 wt% of ammonium bicarbonate powder pore-forming agent are added to a three-dimensional mixer and mixed for 2 hours. The mixer speed is set to 200 r / min and the stirring temperature is maintained at 30° C. to obtain a uniformly dispersed powder mixture of ~30 μm (active substance + binder + pore-forming agent = 100%).
[0034] (3) The powder mixture obtained in step (2) is crushed using a jet mill, the pressure of the jet mill is set to 0.6 MPa, and the working gas is nitrogen to prevent oxidation of the powder. The powder obtained after crushing has a uniform particle size distribution in the range of 3-8 μm.
[0035] (4) The crushed powder mixture was extruded through a twin-screw extruder with the extrusion temperature set at 80° C., the extrusion speed set at 20 mm / s, and the screw speed set at 60 rpm to finally obtain a sheet with a thickness of 300 μm.
[0036] (5) The obtained sheet was passed through a calender and rolled at 100°C with a rolling pressure of 20 MPa and a roller speed of 10 rpm. Finally, the sheet was pressed into a 200 μm thick electrode film with a compaction density of 250 mg cm -3 .
[0037] (6) The rolled electrode film is placed in a vacuum drying oven, the temperature is set to 150°C, the drying time is 6 hours, and the vacuum degree is maintained at 20 kPa. The ammonium bicarbonate is decomposed and released by heating to form a porous structure electrode.
[0038] Comparative Example 1: The process and conditions are the same as those of Example 1, except that the same FeCoNi high entropy alloy powder active material and PTFE binder are used in a mass ratio of 18:1, no pore-forming agent is added, and there is no step (2) and step (3) in Example 1. The powder mixture obtained in step (1) is directly crushed by a jet mill. The mixing time, temperature and rotation speed of step (1) are the same as those in Example 1.
[0039] The mercury intrusion test results show that the porosity of the porous electrode of Example 1 is 46%, and the pore size distribution is concentrated in the range of 3-7 μm. The porosity of Comparative Example 1 is 21%, and the pore size distribution is concentrated in the range of 25-37 μm.
[0040] The electrodes (anode film) and anode diffusion layer (nickel felt) prepared in Example 1 and Comparative Example 1 were mixed with PiperION TM A40 anion exchange membrane, platinum black carbon paper cathode (platinum black content 2.0mg / cm 2 , Fuel cell, 11060028) cathode was assembled into an electrolytic cell, the electrolyte was 1M KOH aqueous solution, the test temperature was 25°C, and the cell voltage was set to 2V.
[0041] The electrodes (anode film) prepared in Example 1 and Comparative Example 1, the anode diffusion layer (nickel foam), and the PiperION TM A40 anion exchange membrane, platinum black carbon paper cathode (platinum black content 2.0mg / cm 2 , Fuel cell, 11060028) to form an anion exchange membrane water electrolyzer, the electrolyte is 1M KOH solution. Figure 2 It can be seen that when the electrolytic cell of Example 1 is under a cell voltage of 2V, the reaction current density is as high as 1.1A cm -2 Under the same working conditions, compared with comparative example 1 (0.73Acm -2 ), Example 1 increased the current density by 51%. This highlights the advantages of the porous dry electrode preparation method in improving electrolyte permeability, gas diffusion and water electrolysis efficiency.
[0042] Example 2
[0043] A method for preparing a porous dry electrode for use in the field of water electrolysis:
[0044] (1) 85 wt% of nickel-cobalt alloy (NiCo) powder active material (particle size 50-150 μm, Xi'an Fangke New Materials) and 7 wt% of polyvinylidene fluoride (PVDF) powder binder were added to a three-dimensional mixer, and the mixing time was set to 2.5 hours, the speed was 400 r / min, and the stirring temperature was maintained at 30° C. The active material and the binder were fully and evenly dispersed by mixing to obtain a uniform powder mixture.
[0045] (2) Add 8 wt % of potassium hydroxide solid powder (pore former) to the powder mixture obtained in step (1), and continue mixing for 2 hours at a rotation speed of 300 r / min and a stirring temperature maintained at 30° C. to finally obtain a uniform powder mixture (active substance + binder + pore former = 100%).
[0046] (3) The powder mixture obtained in step (2) is crushed using a jet mill, the pressure of the jet mill is set to 0.6 MPa, and nitrogen is used as the working gas to avoid oxidation of the powder. The powder particle size distribution after crushing is 3-10 μm, and a uniform powder is obtained.
[0047] (4) The crushed powder mixture was extruded through a twin-screw extruder at 70° C. The screw speed was set to 50 rpm and the extrusion speed was 15 mm / s, finally forming an electrode film with a thickness of 500 μm.
[0048] (5) The extruded electrode film was rolled by a calender at 100°C, with a rolling pressure of 20 MPa, a roller distance of 200 μm, and a compaction density of 300 mg cm -3 .
[0049] (6) The rolled electrode film is immersed in a 1M KOH solution for 12 hours, and the solution temperature is maintained at 25° C. The KOH powder gradually dissolves in the solution and seeps out of the electrode, thereby forming a uniform pore structure electrode inside the electrode.
[0050] The porosity of the prepared electrode membrane is 44% and the pore size distribution is between 2-6μm through mercury intrusion testing. This pore structure helps to enhance the permeability of the electrolyte and the diffusion performance of the gas, thereby improving the electrolysis efficiency of the electrode. The prepared electrode (anode electrode membrane) is combined with nickel felt (as the anode diffusion layer), Fumatech TM Fumasep FAA-3-50 anion exchange membrane and Pt / C cathode (20% Pt on Vulcan XC-72R, Pt loading of 1 mg cm -2 ) was assembled into a complete anion exchange membrane water electrolyzer, and the electrolyte used was 1M KOH aqueous solution. At a cell voltage of 2V, the reaction current density reached 1.02Acm -2 , showing high catalytic activity and water electrolysis efficiency.
[0051] Example 3
[0052] A method for preparing a porous dry electrode for use in the field of water electrolysis, comprising the following steps:
[0053] (1) 90 wt% of FeNi alloy powder active material (particle size of about 30 μm) and 5 wt% of polyvinylidene fluoride (PVDF) powder binder were added to a three-dimensional mixer, and the mixing time was set to 2.5 hours, the speed was 400 r / min, and the stirring temperature was set to 25° C. The powder and the binder were fully dispersed by uniform mixing to obtain a uniform powder mixture.
[0054] (2) Add 5 wt% of ammonium bicarbonate powder (as a pore former) to the mixture obtained in step (1), and continue mixing in a three-dimensional mixer for 2 hours, reducing the speed to 200 r / min, and maintaining the stirring temperature at 25° C. Ensure that the pore former and the active substance are evenly mixed to avoid agglomeration of the pore former (active substance + binder + pore former = 100%).
[0055] (3) The powder mixture obtained in step (2) is crushed by a jet mill, the pressure is set to 0.5 MPa, and nitrogen is used as a protective gas to prevent oxidation of the powder. The powder particle size distribution after crushing is uniform, ranging from 3 to 8 μm, ensuring the uniformity of subsequent sheet forming.
[0056] (4) The crushed powder mixture was extruded through a twin-screw extruder. The extrusion temperature was set at 60° C., the screw speed was set at 50 rpm, and the extrusion pressure was maintained at 2.5 MPa to obtain a sheet with a thickness of 400 μm.
[0057] (5) The extruded sheet was rolled by a calender with the temperature set at 80°C, the rolling pressure at 15 MPa, and the roller speed set at 10 rpm. Finally, the sheet was rolled to a thickness of 250 μm.
[0058] (6) The rolled electrode sheet is placed in a vacuum drying oven for drying, the drying temperature is set to 150°C, the drying time is 12 hours, and the vacuum degree is maintained at 0.05 MPa. Ammonium bicarbonate decomposes and escapes during the drying process to form a porous structure electrode.
[0059] Comparative Example 3: The process and conditions are the same as those of Example 3, except that the same FeNi alloy powder active material and PVDF binder are used in a mass ratio of 18:1, no pore-forming agent is added, and there is no step (2) and step (3) in Example 3. The powder mixture obtained in step (1) is directly crushed by a jet mill. The mixing time, temperature and rotation speed of step (1) are the same as those of Example 3. Step (5) is extruded by a twin-screw extruder, and the sheet thickness is set to 400 μm, which is then rolled to 250 μm by a calender. The extrusion temperature, extruded pole piece thickness, rolling temperature, rolling pressure, and rolled pole piece thickness of steps (5) and (6) are the same as those of Example 3.
[0060] After the mercury intrusion test, the porosity of the electrode sheet of Example 3 was 42%, and the pore size distribution was concentrated in the range of 6-10 μm. The porosity of the electrode sheet of the control group was only 18%, and the pore size distribution was concentrated in the range of 40-60 μm.
[0061] The electrodes (anode film) prepared in Example 3 and the comparative group were combined with stainless steel felt (as anode diffusion layer), Fumatech TM Fumasep FAA-3-50 anion exchange membrane, Pt / C cathode (20% Pt on Vulcan XC-72R, Pt loading of 1 mg cm -2 ) was assembled into an electrolytic cell, the electrolyte was 1M KOH aqueous solution, the cell temperature was set to 50°C, and the voltage was 1.9V. The test results showed that the current density of Example 3 reached 0.8A / cm 2 , showing high catalytic activity and water electrolysis efficiency. In contrast, the current density of the control group was only 0.42A / cm 2 , the performance is significantly worse, highlighting the significant advantages of pore formers in improving electrolyte permeability and gas diffusion.
[0062] Example 4
[0063] (1) 60 wt % of nickel powder active material (~50 μm, Jiangsu Rainey Metal Technology Co., Ltd.) and 20 wt % of polyvinylidene fluoride (PVDF) binder were added to a three-dimensional mixer. The mixing time was set to 0.5 h, the speed was 20 r / min, and the stirring temperature was set to 20 ° C to ensure that the powder and the binder were evenly mixed.
[0064] (2) Add 20 wt% of ammonium bicarbonate powder pore-forming agent to the mixture, mix for 0.5 h, rotate at 50 r / min, and keep the stirring temperature at 20° C. to ensure that the pore-forming agent and the powder are evenly mixed (active substance + binder + pore-forming agent = 100%).
[0065] (3) The mixture was pulverized using an air flow pulverizer, the air flow pressure was set to 0.3 MPa, and the powder particle size distribution was 10 μm.
[0066] (4) A twin-screw extruder was used to extrude a sheet at 20°C with a thickness of 200 μm.
[0067] (5) The sheet was rolled at 50°C using a roller press, and the final thickness of the sheet was 10 μm and the compaction density was 40 mg / cm 3 .
[0068] (6) Dry in a vacuum drying oven at 70°C for 10 hours with the vacuum degree controlled at 0.02 MPa.
[0069] The electrode (anode film) prepared in Example 4 was mixed with nickel foam (anode diffusion layer) and Fumatech TM Fumasep FAA-3-50 anion exchange membrane, Pt / C cathode (20% Pt on Vulcan XC-72R, Pt loading of 1 mg cm -2 ) was assembled into an electrolytic cell, the electrolyte was 1M KOH aqueous solution, the cell temperature was set to 60°C, and the voltage was 2V. The test results showed that the current density of Example 4 reached 0.46A / cm 2 .
[0070] Example 5
[0071] (1) 80 wt% of nickel-cobalt alloy powder (~16 μm) and 10 wt% of PTFE were added to a three-dimensional mixer. The mixing time was set to 2.5 hours, the rotation speed was 400 r / min, and the stirring temperature was 50°C.
[0072] (2) 10 wt % of ammonium carbonate powder pore-forming agent was added to the mixture, the mixing time was 1 hour, the rotation speed was 200 r / min, and the stirring temperature was 50° C.
[0073] (3) A jet mill was used with the pressure set to 0.5 MPa and the particle size after pulverization was 5 μm.
[0074] (4) A sheet with a thickness of 500 μm was extruded at 50° C. using a twin-screw extruder.
[0075] (5) Rolling at 100°C with a roller press, the final sheet thickness is 200 μm and the compaction density is 250 mg / cm 3 .
[0076] (6) Dry in a vacuum drying oven at 120°C for 12 hours with the vacuum degree controlled at 0.03 MPa.
[0077] The electrode prepared in Example 5 was mixed with nickel foam (as anode diffusion layer), Fumatech TM Fumasep FAA-3-50 anion exchange membrane, Pt / C cathode (20% Pt on Vulcan XC-72R, Pt loading of 1 mg cm -2 ) was assembled into an electrolytic cell, the electrolyte was 1M KOH aqueous solution, the cell temperature was set to 60°C, and the voltage was 2V. The test results showed that the current density of Example 5 reached 0.85A / cm 2 .
[0078] Example 6
[0079] (1) 96 wt % of FeCoNi alloy powder (~20 μm) and 2 wt % of PVDF were added into a mixer and mixed for 5 hours at a speed of 1000 r / min and a stirring temperature of 80°C.
[0080] (2) Add 2 wt% of urea pore-forming agent and mix for 2 hours at a speed of 800 r / min and a temperature of 80°C.
[0081] (3) The powder was crushed using a jet mill with the air flow pressure set to 0.8 MPa. The particle size distribution after crushing was 10 μm.
[0082] (4) A sheet having a thickness of 1000 μm was extruded at 80° C. using a twin-screw extruder.
[0083] (5) Roller press at 120°C to a sheet thickness of 500 μm and a compaction density of 500 mg / cm 3 .
[0084] (6) Dry in a vacuum oven at 180°C for 24 hours with the vacuum degree maintained at 0.05 MPa. TM Fumasep FAA-3-50 anion exchange membrane, Pt / C cathode (20% Pt on Vulcan XC-72R, Pt loading of 1 mg cm -2 ) was assembled into an electrolytic cell, the electrolyte was 1M KOH aqueous solution, the cell temperature was set to 60°C, and the voltage was 2V. The test results showed that the current density of Example 6 reached 1.3A / cm 2 .
Claims
1. A method for preparing a porous dry electrode for electrolysis of water, characterized in that: The preparation steps are as follows: (1) adding powdered active substance and powdered binder into a mixer for mixing for 0.5-5h at a speed of 20-1000r / min and a stirring temperature of 20-80°C to obtain a powdered mixture; (2) adding a pore-forming agent to the powder mixture obtained in step (1), mixing the mixture in a mixer for 0.5-2 h at a rotation speed of 50-800 r / min and a stirring temperature of 20-80° C. to obtain a powder mixture; (3) crushing the powder mixture obtained in step (2) by a jet mill, wherein the particle size of the powder after crushing is controlled to be 3-10 μm, to obtain a powder mixture of active material, binder and pore-forming agent; (4) the powder mixture obtained in step (3) is passed through a twin-screw extruder or an open mill to provide high shear force to fiberize the powder binder to obtain a sheet with a thickness of 200-1000 μm; the extrusion temperature is controlled at 20-80° C. and the shear rate is 50-200 rpm; (5) The sheet obtained in step (4) is rolled by a roller press, the temperature is controlled at 50-120°C, the rolling pressure is 5-50 MPa, and finally the sheet is pressed into a 10-500 μm thick electrode film with a compaction density of 40.0-500.0 mg / cm 3 ; (6) Finally, the electrode film obtained in step (5) is treated by one of the following methods to obtain a porous dry electrode: a) When the pore-forming agent added in step (2) is a pore-forming agent, the electrode film is subjected to a heating and drying treatment, so that the pore-forming agent decomposes and escapes from the electrode film at 70-180° C. to form a porous structure electrode, and the drying time is controlled within 10-24 hours; the pore-forming agent is one or a mixture of two or more of ammonium bicarbonate, ammonium carbonate, urea or oxalic acid; Or, b) when the pore former is an electrolyte solute powder in the electrolysis water application, the electrolyte solute powder in the electrode membrane is dissolved in the solution by immersing the electrode membrane in a solution containing the same electrolyte to form a porous structure electrode, and the immersion time is controlled at 12-48 hours; the electrolyte solute powder in the electrolysis water application is one or two of KOH, NaOH or LiOH.
2. The preparation method according to claim 1, characterized in that: In the powder mixture obtained in step (2), The material composition is: 60wt%-96wt% powder active substance, 2wt%-20wt% powder binder, 2wt%-20wt% pore former; The preferred material composition is: 80wt%-90wt% powder active substance, 5wt%-10wt% powder binder, 5wt%-10wt% pore former; More preferably, the material composition is: 85wt%-90wt% powder active substance, 5wt%-8wt% powder binder, 5wt%-7wt% pore former; The powder active material is one or more of nickel (Ni), cobalt (Co), iron (Fe), nickel-cobalt alloy (NiCo), nickel-iron alloy (NiFe), cobalt-iron alloy (CoFe), and nickel-cobalt-iron alloy (NiCoFe); The powder binder is one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polystyrene (PS), ethylene-tetrafluoroethylene copolymer (ETFE), and polyvinyl fluoride (PVF).
3. The preparation method according to claim 1, characterized in that: In step (3), the air flow mill is used for pulverization: the pressure is controlled at 0.3-0.8 MPa, and the working gas is one or more of nitrogen or other inert gases (such as argon) to prevent oxidation of the material.
4. The preparation method according to claim 1, characterized in that: The heating and drying in step (6) a) is vacuum drying, the heating and drying temperature is 70-180° C., the heating and drying time is 10-24 hours, and the vacuum degree is controlled at 0.01-80 kPa to prevent oxygen in the air from reacting with the electrode material and maintain the chemical stability of the material.
5. The preparation method according to claim 1, characterized in that: The pore former is a solute powder of the electrolyte used in the electrolysis of water, preferably one or more of KOH, NaOH or LiOH, used for pore formation in the electrode structure and electrolyte penetration; the mass concentration of the electrolyte in the solution is 0.5-8M.
6. The preparation method according to claim 1 or 5, characterized in that: The contact treatment method between the electrode and the electrolyte includes: immersing the electrode membrane alone in the electrolyte solution, or assembling the electrode membrane as an electrode as a part of the electrolytic cell, and circulating the electrode membrane through the electrolyte solution circulation channel of the electrolytic cell to make the electrode membrane contact with the electrolyte solution; the immersion or circulation time is 12-48 hours, and the temperature of the electrolyte solution is controlled at 25-90°C.
7. An electrode sheet prepared by the preparation method according to any one of claims 1 to 5.
8. Use of the electrode sheet according to claim 7 as an anode in electrolysis of water.
Citation Information
Patent Citations
Dry method for preparing lithium battery positive and negative plates
CN112420986A
Preparation method of self-supporting pole piece and dry-method electrode pole piece
CN115548243A
Method for preparing thick electrode based on dry method membrane preparation process
CN117936686A